1991
DOI: 10.1111/j.1440-6055.1991.tb00441.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF TEMPERATURE ON DEVELOPMENT, SURVIVAL, LONGEVITY AND FECUNDITY OF TRISSOLCUS OENONE DODD (HYMENOPTERA: SCELIONIDAE)

Abstract: The effect of temperature on the rate of development of Trissolcus oenone was determined by rearing individuals on eggs of Biprorulus bibax Breddin under a range of constant temperatures (12.5-35.0OC).Rates of development changed in a linear fashion over a wide range of temperatures. The lower developmental threshold was estimated to be 12.4"C and an estimated 165.5 degree-days were required for egg-adult development. Survival of developing parasitoids ranged between 60-90Vo at most temperatures.Wasps produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 10 publications
4
14
0
2
Order By: Relevance
“…Foerster & Nakama (2002) found that the mean longevity of T. basalis and T. podisi transferred from 25ºC to 15ºC one day before the predicted date for emergence was of about five months; this value is lower than the results obtained in this work. Longevity of T. basalis and T. podisi at 15ºC was also higher than that of other Scelionidae species such as Ceratobaeus masneri Austin (Austin, 1984) and Trissolcus oenone (Dodd) (James & Warren, 1991).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Foerster & Nakama (2002) found that the mean longevity of T. basalis and T. podisi transferred from 25ºC to 15ºC one day before the predicted date for emergence was of about five months; this value is lower than the results obtained in this work. Longevity of T. basalis and T. podisi at 15ºC was also higher than that of other Scelionidae species such as Ceratobaeus masneri Austin (Austin, 1984) and Trissolcus oenone (Dodd) (James & Warren, 1991).…”
Section: Resultsmentioning
confidence: 86%
“…Parasitoids stored at earlier stages of pupal development spent more energy to complete their development and, therefore, their longevity was shorter. Similarly, the longevity of females of T. oenone that emerged at 15ºC was lower than of those that emerged at 17.5ºC (James & Warren, 1991). Adults of T. basalis emerging at 15ºC were small, inactive and survived less than one day (Orr et al, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…No Sul do Paraná, face à maior severidade do inverno, esses parasitóides devem apresentar adaptações fisiológicas que possibilitam sua sobrevivência em condições climáticas desfavoráveis, uma vez que, em zonas temperadas, seus hospedeiros hibernam no estágio adulto (Kiritani et al 1966), induzidos por fotofases curtas (Ali & Ewiess 1977). Das espécies de Scelionidae investigadas, apenas Trissolcus oenone (Dodd) completou o desenvolvimento a 15°C (James & Warren 1991), enquanto que em T. basalis e Telenomus chloropus Thomson, apenas uma pequena proporção de adultos conseguiu emergir (Orr et al 1985). Através da dissecação dos ovos parasitados, Jubb & Watson (1971) e Yeargan (l983) verificaram que Telenomus utahensis Ashmead e Trissolcus euschisti (Ashmead) estocados a 15°C no estágio de ovo, completaram o seu desenvolvimento, sem no entanto conseguirem emergir.…”
unclassified
“…In contrast, corresponding data for the egg parasitoid, Trissolcus oenone Dodd, a natural enemy with a high host specificity for B. bibax, show development times which are 3-4 times faster than B. bibax (James & Warren, 1991). The rate of development of this wasp averages 9 % per day at temperatures between 25 and 30 *C.…”
Section: Discussionmentioning
confidence: 59%
“…This compares to 3 generations for B. bibax (James, 1990b) and 11.2 generations for T. oenone (James & Warren, 1991) during the same period. Mardoeh et al (1985) described 2 strategies by which a natural enemy may control a pest in a non-equilibrium state, which they termed ~ lying in wait )) and ~ search and destroy )).…”
Section: Discussionmentioning
confidence: 83%